2009
DOI: 10.1254/jphs.09076fp
|View full text |Cite
|
Sign up to set email alerts
|

The Chondroprotective Agent ITZ-1 Inhibits Interleukin-1β–Induced Matrix Metalloproteinase–13 Production and Suppresses Nitric Oxide–Induced Chondrocyte Death

Abstract: Abstract. In a screening program aimed at discovering anti-osteoarthritis (OA) drugs, we identified an imidazo [5,1-c] [1,4]thiazine derivative, ITZ-1, that suppressed both interleukin-1β (IL-1β)-induced proteoglycan and collagen release from bovine nasal cartilage in vitro and suppressed intra-articular infusion of IL-1β-induced cartilage proteoglycan degradation in rat knee joints. ITZ-1 did not inhibit enzyme activities of various matrix metalloproteinases (MMPs), which have pivotal roles in cartilage degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…Recent literatures suggest that IL-1β mediated expression of MMPs has been regulated through the activation of MAPKs including ERK, p38 kinase, and JNK signal transduction molecules [37]. Therefore, we determined whether Wogonin mediate its chondroprotective effects through the suppression of MAPKs by measuring the phosphorylation levels of ERK, JNK and p38 in IL-1β stimulated OA chondrocytes.…”
Section: Resultsmentioning
confidence: 97%
“…Recent literatures suggest that IL-1β mediated expression of MMPs has been regulated through the activation of MAPKs including ERK, p38 kinase, and JNK signal transduction molecules [37]. Therefore, we determined whether Wogonin mediate its chondroprotective effects through the suppression of MAPKs by measuring the phosphorylation levels of ERK, JNK and p38 in IL-1β stimulated OA chondrocytes.…”
Section: Resultsmentioning
confidence: 97%
“…IL-1β-induced expression of MMPs has been shown to be mediated by activation of the family of MAPKs including ERK, p38 kinase, and JNK27282930. To evaluate the mechanisms responsible for the F4 mediated suppressive effects, we examined the effects of F4 on MAPK signaling cascade by measuring the phosphorylation levels of ERK, JNK and p38 in IL-1β stimulated OA chondrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The MAPK pathway is comprised of ERK1/2, p38 and the JNK family. Other studies have demonstrated that IL-1β induces the release of MMP3 and MMP13 by articular chondrocytes through the activation of ERK1/2 (9,19,20). On the other hand, the MAPK/ERK pathway is also involved in IL-1β-induced decrease in type II collagen and aggrecan expression in chondrocyte-laden agarose constructs (21).…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies have indicated that the mitogen-activated protein kinase (MAPK) pathway is a fundamental pathway for IL-1β-induced catabolic factor gene transcription in articular chondrocytes (9,(17)(18)(19). The MAPK pathway is comprised of ERK1/2, p38 and the JNK family.…”
Section: Introductionmentioning
confidence: 99%